Does an Index Composed of Clinical Data Reflect Effects of Inflammation, Coagulation, and Monocyte Activation on Mortality Among Those Aging With HIV? - Justice, Amy C.; Freiberg, Matthew S.; Tracy, Russ; Kuller, Lew; Tate, Janet P.; Goetz, Matthew Bidwell; Fiellin, David A.; Vanasse, Gary J.; Butt, Adeel A.; Rodriguez-Barradas, Maria C.; Gibert, Cynthia; Oursler, Kris Ann; et al. (Clinical infectious diseases, 2012)
Background. When added to age, CD4 count and human immunodeficiency virus type 1 (HIV-1) RNA alone (Restricted Index), hemoglobin, FIB-4 Index, hepatitis C virus (HCV), and estimated glomerular filtration rate improve prediction of mortality. Weighted and combined, these 7 routine clinical variables constitute the Veterans Aging Cohort Study (VACS) Index. Because nonroutine biomarkers of inflammation (interleukin 6 [IL-6]), coagulation (D-dimer), and monocyte activation (sCD14) also predict mortality, we test the association of these indices and biomarkers with each other and with mortality. Methods. Samples from 1302 HIV-infected veterans on antiretroviral therapy were analyzed. Indices were calculated closest to date of collection. We calculated Spearman correlations stratified by HIV-1 RNA and HCV status and measured association with mortality using C statistics and net reclassification improvement (NRI). Results. Of 1302 subjects, 915 had HIV-1 RNA <500 copies/mL and 154 died. The VACS Index was more correlated with IL-6, D-dimer, and sCD14 than the Restricted Index (P < .001). It was also more predictive of mortality (C statistic, 0.76; 95% confidence interval [CI], .72-.80) than any biomarker (C statistic, 0.66-0.70) or the Restricted Index (C statistic, 0.71; 95% CI, .67-.75). Compared to the Restricted Index alone, NRI resulted from incremental addition of VACS Index components (10%), D-dimer (7%), and sCD14 (4%), but not from IL-6 (0%). Conclusions. Among HIV-infected individuals, independent of CD4, HIV-1 RNA, and age, hemoglobin and markers of liver and renal injury are associated with inflammation. Addition of D-dimer and sCD14, but not IL-6, improves the predictive accuracy of the VACS Index for mortality.